2008
DOI: 10.4067/s0034-98872008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Cirugía de la endocarditis infecciosa en un centro regional en Chile: Análisis de casos y resultados en el largo plazo

Abstract: Surgery for bacterial endocarditis. Retrospective study of 32 patients Background: Surgery for active endocarditis is indicated in cases of congestive heart failure (CHF), persistent sepsis, systemic embolization and paravalvular involvement. Aim: To assess and report the long term results of surgery in adult patients. Patients and methods: Retrospective review of clinical records and operative procedures of 32 patients aged 43±13 years (28 women) subjected to reparative surgery for complications of endocardit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
1
0
3
Order By: Relevance
“…One study comprised 2 reports, but both were included since one reported data on clinical and imaging characteristics (Casabe et al, 1996b) and the other reported data on microorganisms and further clinical manifestations (Casabe et al, 1996a). We treated this study as one throughout the review leading to 44 studies(Allende González et al, 2020;Avellana et al, 2018;Bahamondes et al, 2008;Bezerra et al, 2020;Burgos et al, 2019;Casabe et al, 1996b;Corral et al, 1993;Cremona et al, 2007;Damasco et al, 2014;Ediap et al, 2017;Ferreiros et al, 2006;Flores et al, 2017;Fragomeni et al, 2003;Fránquiz Cuéllar and Alvarez Ozambela, 1986;Holanda et al, 2015;Jacob Filho et al, 1988;Jáuregui Camargo et al, 1997;Kaiser et al, 1984;Leyva Quert et al, 2009;Marino et al, 2014;Merello et al, 2019;Monteiro et al, 2017;Murdoch et al, 2009;Negrín Expósito et al, 2003;Nieto et al, 1985;Olaya-Sanchez et al, 2019;de Oliveira et al, 2018;Ortiz et al, 1983;Oyonarte G et al, 2003;Pérez Zerpa et al, 2020;Pinheiro et al, 2018;Pivatto Júnior et al, 2020;Popilovsky et al, 2014;Ris et al, 2019;Romero Flecha and Aveiro Figueredo, 2020;Saito et al, 2014;Siciliano et al, 2014a…”
Section: Study Selectionmentioning
confidence: 99%
“…One study comprised 2 reports, but both were included since one reported data on clinical and imaging characteristics (Casabe et al, 1996b) and the other reported data on microorganisms and further clinical manifestations (Casabe et al, 1996a). We treated this study as one throughout the review leading to 44 studies(Allende González et al, 2020;Avellana et al, 2018;Bahamondes et al, 2008;Bezerra et al, 2020;Burgos et al, 2019;Casabe et al, 1996b;Corral et al, 1993;Cremona et al, 2007;Damasco et al, 2014;Ediap et al, 2017;Ferreiros et al, 2006;Flores et al, 2017;Fragomeni et al, 2003;Fránquiz Cuéllar and Alvarez Ozambela, 1986;Holanda et al, 2015;Jacob Filho et al, 1988;Jáuregui Camargo et al, 1997;Kaiser et al, 1984;Leyva Quert et al, 2009;Marino et al, 2014;Merello et al, 2019;Monteiro et al, 2017;Murdoch et al, 2009;Negrín Expósito et al, 2003;Nieto et al, 1985;Olaya-Sanchez et al, 2019;de Oliveira et al, 2018;Ortiz et al, 1983;Oyonarte G et al, 2003;Pérez Zerpa et al, 2020;Pinheiro et al, 2018;Pivatto Júnior et al, 2020;Popilovsky et al, 2014;Ris et al, 2019;Romero Flecha and Aveiro Figueredo, 2020;Saito et al, 2014;Siciliano et al, 2014a…”
Section: Study Selectionmentioning
confidence: 99%
“…En estudios retrospectivos recientes publicados en el medio nacional, referente a pacientes sometidos a cirugía en EI, que abarcan décadas del ochenta, noventa del siglo XX y comienzos del siglo XXI [59][60][61] , se evidencia en algunos de ellos la alta negatividad en hemocultivos: 47% para el grupo de Temuco 60 , con predominio de estafilococos; 51% de negatividad para el grupo de Concepción 61 , siendo el estafilococo el germen aislado más frecuente pero predominando como grupo os estreptococos. En el trabajo de Zalaquett et al, del grupo de Santiago 59 , por razones metodológicas, todos los paciente que incluye el trabajo tienen hemocultivos positivos, predominando el estreptococo.…”
Section: Seguimientounclassified
“…El tratamiento quirúrgico en las tres series tiene buen resultado a corto y largo plazo 59,60 . Resultados todos comparables con nuestra serie aunque ECNEI es un estudio prospectivo y multicéntrico.…”
Section: Seguimientounclassified
“…La terapia antibiótica tiene un rol crucial en el control y la eliminación de los gérme-nes del organismo y del aparato cardiovascular. A pesar de esto, se requiere frecuentemente de la cirugía tanto para corregir la hemodinamia consecuente al daño valvular, como para erradicar el foco infeccioso 7 . Su desenlace sin tratamiento antibiótico es fatal en prácticamente todos los casos.…”
unclassified